Trade-Offs and Synergies of Ecosystem Services in Terminal Lake Basins of Arid Regions Under Environmental Change: A Case Study of the Ebinur Lake Basin - Guoqing Lv; Yonghui Wang; Xiaofei Ma; Yonglong Han; Chun Luo; Wei Yu; Jian Liu; Zhiyang Du (Land)
As essential components of arid region ecosystems, terminal lakes play a critical role in enhancing the functions of ecosystem services (ESs) and improving ecological structure. Despite the increasing degradation of ESs and landscape stability due to climate and human pressures, comprehensive assessments of water provision, carbon storage, soil conservation, and habitat integrity in arid terminal lake regions are still lacking. Focusing on the Ebinur Lake Basin (ELB), this study employed the InVEST model to quantify ES changes from 2000 to 2020, combined with univariate regression, Pearson, and Spearman correlation analyses to explore their dynamic evolution. Landscape pattern indices calculated via Fragstats 4.2 further revealed trends in fragmentation, boundary complexity, and diversity. Results show that most ESs exhibited synergistic relationships, particularly between carbon sequestration and habitat quality (r = 0.45), observed clear trade-offs, such as between water yield and carbon sequestration (r = −0.47), underscoring the complexity of ecosystem interactions. Enhanced ES functions were associated with increased patch number, density, and shape complexity, while landscape diversity fluctuated. NDVI growth improved ES performance and reduced fragmentation, though changes in landscape metrics were largely driven by climate variability and socio-economic pressures, exacerbating fragmentation and weakening ecological stability. Overall, understanding the trade-offs and synergies among ESs in the ELB is crucial for informing sustainable development strategies.